JENIS BAKTERI DAN JAMUR KONTAMINAN UDARA DI RUANG PERAWATAN SUB BAGIAN PENYAKIT DALAM RUMAH SAKIT UMUM DAERAH BANJARBARU - Yulia Budiarti, Lia; Noormuthmainah, Noormuthmainah; Rahmiati, Rahmiati (Lembaga Penelitian Universitas YARSI, 2007)
Nosocomial infection is one of the major health problem in the world. One of the way for transmitting the causative microorganism of nosocomial infection is airborne. This research had been done to know kinds of air contaminating bacteria in sub departement of internal disease science of General Hospital Banjarbaru. This research was laboratory descriptive using ?open plate? method. The results of research described that there were five kinds of bacteria, they were Staphylococcus epidermidis 38,07%, Escherichia coli 27,52%, Streptococcus ? haemolyticus 19,26%, Pseudomonas aeruginosa 10,55% and Staphylococcus aureus 4,58% and five kinds of fungi: Rhizopus sp. (37,78%), Aspergillus niger (20%), Trichosporon sp. (17,78%), Penicilliumsp. (13,33%) and Aspergillus flavus (11,11%).